2020
DOI: 10.1186/s10020-019-0128-8
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effects of genetically engineered cardiac stem cells by spheroid formation on ischemic cardiomyocytes

Abstract: Background: Sca-1+ cardiac stem cells and their limited proliferative potential were major limiting factors for use in various studies. Methods: Therefore, the effects of sphere genetically engineered cardiac stem cells (S-GECS) inserted with telomerase reverse transcriptase (TERT) were investigated to examine cardiomyocyte survival under hypoxic conditions. GECS was obtained from hTERT-immortalized Sca-1+ cardiac stem cell (CSC) lines, and S-GECS were generated using poly-HEMA.Results: The optimal conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Scaffold-free approaches using spheroids in hanging drop cultures provide similar advantages to EHTs and do not require the addition of foreign material for the fabrication of the cardiac tissue [ 88 , 101 ]. For instance, Jeong et al’s [ 102 ] research showed that genetically engineered antigen-1-positive cardiac stem cells (Sca-1 + CSC lines) secrete paracrine factors such as SDF-1α and have cardioprotective roles described using in vitro spheroids. SDF-1α has demonstrated to protect the ischemic cardiomyocytes by inducing the signaling pathway for cell growth, survival, and protein synthesis in the 3D IRI spheroid heart model [ 102 ].…”
Section: Cardiovascular Models To Mimic Ischemic-reperfusion Injurymentioning
confidence: 99%
“…Scaffold-free approaches using spheroids in hanging drop cultures provide similar advantages to EHTs and do not require the addition of foreign material for the fabrication of the cardiac tissue [ 88 , 101 ]. For instance, Jeong et al’s [ 102 ] research showed that genetically engineered antigen-1-positive cardiac stem cells (Sca-1 + CSC lines) secrete paracrine factors such as SDF-1α and have cardioprotective roles described using in vitro spheroids. SDF-1α has demonstrated to protect the ischemic cardiomyocytes by inducing the signaling pathway for cell growth, survival, and protein synthesis in the 3D IRI spheroid heart model [ 102 ].…”
Section: Cardiovascular Models To Mimic Ischemic-reperfusion Injurymentioning
confidence: 99%
“…Indeed, both allogeneic mesenchymal stem cells and cardiac stem cells, alone or in combination have been tested in preclinical models with positive results and also reached the first-in-man clinical experimentation [43][44][45]. The latter has created the path for the idea of creating "supercargo cells", which is transplantable cellular reservoirs engineered to release multiple cardioprotective and cardio-regenerative factors or small molecules to obtain effective myocardial regeneration [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…5(a) depicts ZnO nanorod growth on seed layers containing grains with several sizes. Since the c-axis is well known as the fastest-growing direction of the hexagonal wurtzite ZnO phase, [27][28][29][30][31] Zn 2+ and OHin a solution are consumed to form ZnO nanorods on the c-plane oriented surfaces on grains. As seen in a SEM image (The second image in Fig.…”
Section: Resultsmentioning
confidence: 99%